Polskie centra kulturalne i naukowe w wieku XVIII: Warszawa, Kraków i… Lipsk - Grzesiuk, Ewa (Studia Europaea Gnesnensia, 2010)
The Saxon times, which set off the apogee of Sarmatism, are habitually seen as a pe-riod of decline culture in Poland. Going against such views, the author demonstrates that already in the middle 18th century Poland there were cultural centres and projects of educational reform. A particular role in the process fell to people-institutions, such as brothers Stanisław and Józef Załuski.